ANALISIS PREDIKSI TINGKAT KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE DAN ZMIJEWSKI PADA PT BAKRIE TELECOM TBK PERIODE 2015-2017 - Suci Ariyani; Djumali Djumali; Ida Aryati (ITB AAS INDONESIA Surakarta, 2019)
The purpose of this research is to know financial condition of Bakrie Telecom Tbk company using Altman and Zmijewski's analysis model period 2015-2017, during the period so its be able to predict financial distress happened inside the company. The data used to this research is secondary data, with population telecommunication companies go public enrolled in the Indonesia Stock Exchange (BEI) period 2015-2017. Data analysis techniques that used is Altman and Zmijewski's dicriminant analysis. The Altman's analysis model classified into three company categories, which are company that is in broken condition, grey area and not bankrupt/healthy. The Zmijewski's analysis model classified into two company categories, which are potentially bankrupt company and unpotentially bankrupt company/health. The results of the Bakrie Telecom Tbk company's financial distress analysis period of 2015-2017 used the Altman's model showed that company was not in bankrupt category/health .The results of the Zmijewski's analysis model showed in 2015 was not in bankrupt category/health category and in the year 2016-2017 was in the bankrupt category. Keywords: Bankruptcy , Altman , Zmijewski